2004
DOI: 10.1021/ol047835p
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of β-Hydroxyketones by SmI2/H2O/Et3N

Abstract: Reduction of a series of beta-hydroxyketones by SmI2/H2O/Et3N provided 1,3-diols in quantitative yields. The reactions were exceedingly clean with no byproduct formation, negating the need for further purification. Most reactions provided moderate to excellent diastereoselectivity with syn-diols as the major isomer in most instances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
1
19
0
1
Order By: Relevance
“…Mixtures of water/amine have proven to be one of most efficient and potent additives to carry out reductions of a range of substrates . Hilmersson and others carried out seminal work in this area increasing the substrate scope of this additive . The scope of this additive was further improved by Procter and Szostak who demonstrated that substrates such as carboxylic acid derivatives typically recalcitrant to electron transfer can be reduced by SmI 2 /water/amine .…”
Section: Resultsmentioning
confidence: 99%
“…Mixtures of water/amine have proven to be one of most efficient and potent additives to carry out reductions of a range of substrates . Hilmersson and others carried out seminal work in this area increasing the substrate scope of this additive . The scope of this additive was further improved by Procter and Szostak who demonstrated that substrates such as carboxylic acid derivatives typically recalcitrant to electron transfer can be reduced by SmI 2 /water/amine .…”
Section: Resultsmentioning
confidence: 99%
“…Zçrb and Brückner reported that SmBr 2 mediates a novel reduction of acetonides (generated by Sharpless asymmetric dihydroxylation) to give enantiomerically pure 3-hydroxy ketones (Scheme 7). [21] Furthermore, by applying the established protocol for the diastereoselective reduction of hydroxy ketones, [22] the reaction was extended to the synthesis of 1,3-anti diols with good selectivity.…”
Section: Samarium(ii) Bromidementioning
confidence: 99%
“…The α,β‐unsaturated nitroalkenes were directly reduced into saturated amines and substrates that contained halide, ether, allyl ether, benzyl, or indole moieties were tolerated under these reduction conditions. Moreover, the utility of this SmI 2 /water/amine reagent system has been established for the rapid and selective reduction of alkyl and aryl halides, α,β‐unsaturated esters, conjugated olefins, β‐hydroxyketones, imines, allyl ethers, and hydrocarbons in up to quantitative yield.…”
Section: Functional‐group Transformationsmentioning
confidence: 99%